Key Resonance Component Evaluation of Medium-Voltage Power Systems - Zikang ZHOU; Shun TAO; Chaofan XUE; Wei YUAN; Yonghai XU (Zhongguo dianli, 2024)
Modal analysis techniques can capture the most comprehensive harmonic resonance data. Although current sensitivity analysis methodologies can rank the impact that each electronic component has on resonance, they fall short in precisely pinpointing the key resonant components and circuits. Initially, an explanation of the physical significance of the contributing factors is offered following the derivation, and two existing sensitivity analysis methods are summarized. Subsequently, taking into account the diversity in the value ranges of components with different attributes, as well as the effects of the external characteristics of inverters, a novel identification method is introduced. This method is tailored for pinpointing critical resonant elements and circuits within power distribution networks. The method's precision in identifying vital resonant components is corroborated through analytical examples and PSCAD simulation outcomes. This technique provides an accurate means to discern the critical components that drive systemic inherent resonance, serving as a valuable resource for the study and mitigation of harmonic resonance issues, as well as for post-incident analyses.